Menjadi Guru Profesional di Era Kurikulum Merdeka: Upaya dan Tantangan di SMP - Elvina, Julia; Putri, Meylani Eka; Sari, Suci Rahma; Irma, Ade (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2025)
This study examines the efforts and challenges of SMP Negeri 2 Tambang teachers in implementing the Merdeka Curriculum. The qualitative method with a case study approach was used through in-depth interviews with three teachers and document analysis. The results showed three main strategies carried out by teachers: (1) participating in training such as In House Training and the Guru Penggerak program, (2) utilizing digital learning technology, and (3) strengthening collaboration through the MGMP forum. However, the implementation of this curriculum faces challenges in the form of heavy administrative burdens, gaps in understanding among teachers, and limited technological infrastructure. Based on these findings, the study recommends: (1) simplifying administration, (2) training tailored to teachers' needs, and (3) improving technological facilities. This study concludes that teacher professionalism in the Merdeka Curriculum era requires the ability to adapt to change and build collaboration to create student-centered learning. The successful implementation of this curriculum requires systemic support from various education stakeholders.